Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Produk Dan Kualitas Pelayanan Di Mie Gacoan Kartasura - Bilal Achmad Zaki Ramadhan; Daryanti Daryanti; Nur Safitri; Umi Nur Khasanah; Missyel Rosdiana Eviyani; Anggi Ratnawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Consumer satisfaction is a consumer feeling, both in the form of pleasure and disappointment that arises from comparing and evaluating a product related to consumer expectations for the product. The purpose of this study is to determine the level of consumer satisfaction with product attributes, in this case Mie Gacoan Kartasura, which can then be used as material for evaluating the company’s busiiness program as a considerationin in determining future policies. This research is a type of quantitative research using a combination of primary data sources (distribution of questionnaires) and secondary (literature study) using descriptive analysis techniques, IPA (Importance Performance Analysis), and CSI (Customer Satisfaction Index). The results of data analysis in this study indicate that consumers are satisfied with the product quality and service of Mie Gacoan Kartasura.